2019
DOI: 10.1084/jem.20180729
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Tbk1 loss has opposing effects in early and late stages of ALS in mice

Abstract: Heterozygous loss-of-function mutations of TANK-binding kinase 1 (TBK1) cause familial ALS, yet downstream mechanisms of TBK1 mutations remained elusive. TBK1 is a pleiotropic kinase involved in the regulation of selective autophagy and inflammation. We show that heterozygous Tbk1 deletion alone does not lead to signs of motoneuron degeneration or disturbed autophagy in mice during a 200-d observation period. Surprisingly, however, hemizygous deletion of Tbk1 inversely modulates early and late disease phases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 44 publications
(62 reference statements)
9
44
0
Order By: Relevance
“…Heterozygous deletion of the α-IFN receptor Ifnar1 significantly prolongs the life span of SOD1G93A ALS mice (Wang et al, 2011). In a 2019 study, Brenner et al (2019) further elucidated on the connection between TBK1 and SOD1 in the mouse models. The group showed that at the early stage, heterozygous Tbk1 deletion impairs autophagy in motoneurons and prepones the clinical onset and muscular denervation in SOD1G93A/Tbk1 ± mice, while at the late disease stage, it significantly alleviates microglial neuroinflammation, decelerates disease progression, and extends mouse survival (Brenner et al, 2019).…”
Section: Tank-binding Kinase 1 (Tbk1)mentioning
confidence: 99%
“…Heterozygous deletion of the α-IFN receptor Ifnar1 significantly prolongs the life span of SOD1G93A ALS mice (Wang et al, 2011). In a 2019 study, Brenner et al (2019) further elucidated on the connection between TBK1 and SOD1 in the mouse models. The group showed that at the early stage, heterozygous Tbk1 deletion impairs autophagy in motoneurons and prepones the clinical onset and muscular denervation in SOD1G93A/Tbk1 ± mice, while at the late disease stage, it significantly alleviates microglial neuroinflammation, decelerates disease progression, and extends mouse survival (Brenner et al, 2019).…”
Section: Tank-binding Kinase 1 (Tbk1)mentioning
confidence: 99%
“…In ALS patients bearing a TBK1 mutation, it was suggested that the TBK1-induced pathology was caused by a loss of function from haploinsufficiency as TBK1 mRNA and protein levels were reduced in comparison to sporadic ALS patients ( Freischmidt et al , 2015 ; Pottier et al , 2015 ). In mice, TBK1 deficiency is lethal, whereas haploinsufficiency is insufficient to cause the disease by itself ( Brenner et al , 2019 ; Gerbino et al , 2020 ). However, in a mutant hSOD1 model, haploinsufficiency of TBK1 or a loss-of-function mutation in TBK1 R228H showed a biphasic effect on the disease course: accelerating disease onset, but afterwards suppressing the appearance of neurotoxic microgliosis and astrogliosis, and extending survival.…”
Section: How Does Immunity Turn From Friend To Foe During Als?mentioning
confidence: 99%
“…However, in a mutant hSOD1 model, haploinsufficiency of TBK1 or a loss-of-function mutation in TBK1 R228H showed a biphasic effect on the disease course: accelerating disease onset, but afterwards suppressing the appearance of neurotoxic microgliosis and astrogliosis, and extending survival. Primary microglia from TBK1 +/− SOD1 G93A mice exhibited diminished production of proinflammatory cytokines in vitro ( Brenner et al , 2019 ). TBK1 R228H SOD1 G93A mice led to diminished IRF3 activation and decreased induction of IFN-stimulated genes at the late stage of the disease.…”
Section: How Does Immunity Turn From Friend To Foe During Als?mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in mouse brain, TBK1 suppresses RIPK1 activation and downstream neuroinflammation associated with a loss of function phenotype in ALS/FTD (70). Notably, the TBK1 haploinsufficiency phenotype associated with ALS/FTD aggravates autophagy defects and early onset of motor defects, while TBK1 haploinsufficiency at later stages seems to alleviate neuroinflammation and slow disease progression in mice models (71,72). Thus, we recognize that TBK1 likely has key roles in glia and that cell type-specific phenotypes will likely differ upon global inhibition of TBK1 depending on the brain region and disease stage.…”
Section: Discussionmentioning
confidence: 99%